Generation Z and the (new) construction of identity in pandemic and post-pandemic times - Amendola, Alfonso; Guerra, Annachiara; Masullo, Martina (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Generation Z has emotionally misunderstood the forced abandonment of face-to-face social interaction during the lockdown. We examined Generation Z because it is in the midst of its own identity construction. The aim of our essay is to investigate the new fragilities in the pandemic and post-pandemic era and bring to light the new practices of sociability that have emerged in recent years through social media and live streaming platforms such as Twitch.